Social, Cultural, and Environmental Challenges Faced by Children on Antiretroviral Therapy in Zimbabwe: a Mixed Method Study - Margaret Macherera, MSc; Lindani Moyo, BSc; Mkhanyiseli Ncube, BSc; Angella Gumbi, MSc (Global Health and Education Projects, Inc., 2016)
Objectives Despite the advent of antiretroviral therapy (ART), many children, particularly in the rural communities of Zimbabwe, remain vulnerable. The purpose of this study was to determine the factors and challenges facing children on antiretroviral therapy (ART) in Brunapeg area of Mangwe District, Zimbabwe. Methods A mixed-method approach involving interviewer-guided focus group discussions and piloted semi-structured questionnaires was utilized to collect data from different key population groups. The data obtained were analyzed through content coding procedures based on a set of predetermined themes of interest. Results A number of challenges emerged as barriers to the success of antiretroviral therapy for children. Primary care givers were less informed about HIV and AIDS issues for people having direct impact on the success of antiretroviral therapy in children whilst some were found to be taking the antiretroviral drugs meant for the children. It also emerged that some primary care givers were either too young or too old to care for the children while others had failed to disclose to the children why they frequently visited the Opportunistic Infections (OI) clinic. Most primary care givers were not the biological parents of the affected children. Other challenges included inadequate access to health services, inadequate food and nutrition and lack of access to clean water, good hygiene and sanitation. The lack of community support and stigma and discrimination affected their school attendance and hospital visits. All these factors contributed to non-adherence to antiretroviral drugs. Conclusions and Public Health Implications: Children on ART in rural communities in Zimbabwe remain severely compromised and have unique problems that need multi-intervention strategies both at policy and programmatic levels. Effective mitigating measures must be fully established and implemented in rural communities of developing countries in the fight for universal elimination of HIV/AIDS. Key Words: Antiretroviral therapy • Challenges • Children • HIV/AIDS • Mangwe District • Zimbabwe